Role and importance of Korean cultural education in Korean language education: A case study of Malaysian universitiew - Rou, S.Y.; Kim, K.H. (2008)
The goal of this paper is to ascertain the importance and necessity of cultural education in Korean language education. At the first phase of the research, the emphasis is on examining Malaysian students' purpose of learning Korean language as a second foreign language. Our survey reveals that many students are eager to know more aspects of Korean culture such as traditions, customs, costume and food while they are studying Korean language. Subsequently, a second survey is designed to prove necessity of Korean cultural education in Korean language education. The students' knowledge about Korea and Korean culture, their demands on Korean cultural education are highlighted in this survey.